Development and application of an analytical approach to assess an antibody's potential for disulfide reduction. (9th January 2022) - Yang, Yanhong; Bastani, Niutish; Lagler, Sara K.; Harris, Doug; Nagy, Attila; Chen, Peifeng; Patel, Aakash; Li, Yile; Gowetski, Daniel B.; Lei, Q. Paula
Abstract: Monoclonal antibody (mAb) interchain disulfide bond reduction has been observed in a recent large‐scale clinical manufacturing operation. A massive reduction/precipitation at post‐clarification steps has occurred. This note presents the development of a novel analytical approach to identify the "potential reduction"—a unique approach to predict the propensity of a monomeric‐profiled mAb to be reduced in the post‐harvest stage, such as harvest clarification and/or purification steps. The core of this new approach includes comparing the non‐reducing capillary electrophoresis profiles of pre‐ and post‐vacuum treated mAb in harvest cell culture fluid (HCCF). Using this approach, the potential reductions of two in‐house mAbs in the unclarified and clarified cell culture harvest were assessed.